2016
DOI: 10.1353/hpu.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Patients and Caregivers to Design Transitional Care Management Services at a Minority Serving Institution

Abstract: Limited socioeconomic resources contribute to high readmission rates at minority serving institutions (MSIs). A better understanding of patient-level factors and need for patient navigators could inform approaches to enhance care transitions tailored to these vulnerable patient populations. We sought to understand the perspectives of patients and their caregivers about hospital to home transitions from an MSI, as well as their attitudes about patient navigators to facilitate care transitions. We conducted qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This survey describes variation in elements of patient navigation programs nationally but does not evaluate the impact of those differences on patient outcomes. These outcomes range greatly given the breadth of PN interventions; recent studies provide a set of patient navigator tasks for cancer care [28] colorectal cancer screening [51] medical home services for HIV-positive homeless patients [52] transitional care post discharge [53]. A systematic review and meta-analysis of care coordination demonstrated positive results across cancer continuum outcomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…This survey describes variation in elements of patient navigation programs nationally but does not evaluate the impact of those differences on patient outcomes. These outcomes range greatly given the breadth of PN interventions; recent studies provide a set of patient navigator tasks for cancer care [28] colorectal cancer screening [51] medical home services for HIV-positive homeless patients [52] transitional care post discharge [53]. A systematic review and meta-analysis of care coordination demonstrated positive results across cancer continuum outcomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…The role of patient navigators. Studies are also being conducted to evaluate innovative and patient-centered interventions, such as patient navigators (43,61). The PCORI (Patient-Centered Outcomes Research Institute)-funded PArTNER (Patient Navigator to Reduce Readmissions) study is a pragmatic trial testing the role of community health workers serving as patient navigators to reduce anxiety and improve social support (coprimary outcomes); the study examines readmissions as a secondary outcome.…”
Section: Case Presentationsmentioning
confidence: 99%
“…All abstracts were reviewed for exclusion criteria, and studies were removed for the exclusion reasons noted earlier. A total of 12 articles were included in the qualitative metasynthesis, as outlined in the PRISMA chart in Figure 1 (Bakas, Austin, Okonkwo, Lewis, & Chadwick, 2002; Blair, Volpe, & Aggarwal, 2014; Coleman & Roman, 2015; Dossa et al, 2012; Foust et al, 2012; Kangovi et al, 2014; Linton, Ing, Vento, & Nakagawa, 2015; MacLeod, 2011; Naylor, Stephens, Bowles, & Bixby, 2005; Ursan et al, 2016; Werner, Tong, Borkenhagen, & Holden, 2018; White et al, 2015).…”
Section: Resultsmentioning
confidence: 99%